The rabbit hunter - Kepler, Lars (Kepler, Lars. Joona Linna novel., 2020)
Ten little rabbits, all dressed in white,Tried to get to heaven on the end of a kite. Kite string got broken, down they all fell, Instead of going to heaven, they all went to... It begins with a nursery rhyme. Nineteen minutes later you die. A masked stranger stands in the shadows. He watches his victim through the window. He will kill him slowly<U+2014>make him pay. Soon the Rabbit Hunter has claimed another three victims. This predator will stop at nothing to reap his ultimate revenge. It<U+2019>s up to Joona Linna and Saga Bauer to untangle one of the most complex cases of their career, and follow the killer<U+2019>s trail of destruction back to one horrific night of violence.